Statistical analysis using taguchi method for wind turbine in ducting system - A. A.Malik; S. M.Maharum; M.Z. W. Mohd. Tohid; M. K.Rahmat; I. H.Hamzah (Institute of Advanced Engineering and Science, 2019)
Wind turbine is a device that converts kinetic energy of wind into electrical energy. Weak air pressure with an average of 2m/s to 4m/s makes wind turbine implementation in Malaysia becoming difficult and unrealistic. In order to produce a good power and torque, a quality air pressure is needed. Wind turbine performance depends on the incoming wind speed. Fluctuating and low quality air pressure are the significant challenges in wind turbine implementation. There are many types of mechanism and control but the production of output power is still considered low compared to the actual equipment. In a large building, Heat Ventilation Air Conditioning (HVAC) system is highly required to control the indoor temperature and consistent air pressure through ducting. The consistency of air pressure in ducting system make a drive for this research to proposed a wind turbine implementation in ducting system in order to produce electrical energy. In HVAC there are five parameters to be considered in order to identify the air pressure distribution in ducting system. These five parameters are input air pressure, ducting height, distance between blower to the pipe, total effective length and gap between trunk or run out. In this paper, an analysis of air pressure effect in a ducting system will be conducted via a development of air pressure prototype. Thousands of experiments are required with regards to a huge number of experiments to be considered. Spesifically a statistical analysis Taguchi Method is used to reduce a number of experiments. Without statistical analysis, 3125 experiments shall be conducted to identify the air pressure distribution in the ducting system. However, these huge number of experiments are reduced to only 25 experiment by using Taguchi method based on the function of L25 in array orthogonal